<meta http-equiv="refresh" content="1; url=/nojavascript/">
Skip Navigation
You are viewing an older version of this Concept. Go to the latest version.

Multiplication of Monomials by Polynomials

Practice Multiplication of Monomials by Polynomials
Practice Now
Multiplication of Monomials by Polynomials

Did you know that the formula for the volume of a pyramid is V= \frac{1}{3}Bh , where B is the area of the base of the pyramid and h is the pyramid's height? What if the area of the base of a pyramid were x^2 + 6x + 8 and the height were 9x ? What would the volume of the pyramid be? In this Concept, you'll learn how to multiply a polynomial by a monomial so that you can answer questions such as this.


When multiplying polynomials together, we must remember the exponent rules we learned in previous Concepts, such as the Product Rule. This rule says that if we multiply expressions that have the same base, we just add the exponents and keep the base unchanged. If the expressions we are multiplying have coefficients and more than one variable, we multiply the coefficients just as we would any numbers. We also apply the product rule on each variable separately.

Example A

Multiply (2x^2 y^3) \times (3x^2 y) .


(2x^2 y^3) \times (3x^2 y)=(2\cdot3) \times (x^2 \cdot x^2) \times (y^3 \cdot y)=6x^4 y^4

Multiplying a Polynomial by a Monomial

This is the simplest of polynomial multiplications. Problems are like the one above.

Example B

Multiply the following monomials.

(a) (2x^2)(5x^3)

(c) (3xy^5)(-6x^4y^2)

(d) (-12a^2b^3c^4)(-3a^2b^2)


(a) (2x^2)(5x^3)=(2 \cdot 5)\cdot (x^2 \cdot x^3) = 10x^{2+3}=10x^5

(c) (3xy^5)(-6x^4y^2)=-18x^{1+4}y^{5+2}=-18x^5y^7

(d) (-12a^2b^3c^4)(-3a^2b^2) = 36a^{2+2}b^{3+2}c^4=36a^4b^5c^4

To multiply monomials, we use the Distributive Property.

Distributive Property: For any expressions a, \ b , and c , a(b+c)=ab+ac .

This property can be used for numbers as well as variables. This property is best illustrated by an area problem. We can find the area of the big rectangle in two ways.

One way is to use the formula for the area of a rectangle.

Area \ of \ the \ big \ rectangle & = Length \times Width\\Length & = a, \ Width = b + c\\Area & = a \times (b + c)

The area of the big rectangle can also be found by adding the areas of the two smaller rectangles.

Area \ of \ red \ rectangle & = ab\\Area \ of \ blue \ rectangle & = ac\\Area \ of \ big \ rectangle & = ab + ac

This means that a(b+c)=ab+ac .

In general, if we have a number or variable in front of a parenthesis, this means that each term in the parenthesis is multiplied by the expression in front of the parenthesis.

a(b+c+d+e+f+\ldots)=ab+ac+ad+ae+af+ \ldots The “...” means “and so on.”

Example C

Multiply 2x^3 y(-3x^4 y^2+2x^3 y-10x^2+7x+9) .


& 2x^3 y(-3x^4 y^2+2x^3 y-10x^2+7x+9)\\& = (2x^3 y)(-3x^4 y^2 )+(2x^3 y)(2x^3 y)+(2x^3 y)(-10x^2 )+(2x^3 y)(7x)+(2x^3 y)(9)\\& = -6x^7 y^3+4x^6 y^2-20x^5 y+14x^4 y+18x^3 y

Video Review

Guided Practice

Multiply -2a^2b^4(3ab^2+7a^3b-9a+3) .


Multiply the monomial by each term inside the parenthesis:

& -2a^2b^4(3ab^2+7a^3b-9a+3)\\& = (-2a^2b^4)(3ab^2)+(-2a^2b^4)(7a^3b)+(-2a^2b^4)(-9a)+(-2a^2b^4)(3)\\& = -6a^3b^6-14a^5b^5+18a^5b^4-6a^2b^4


Multiply the following monomials.

  1. (2x)(-7x)
  2. 4(-6a)
  3. (-5a^2b)(-12a^3b^3)
  4. (-5x)(5y)
  5. y(xy^4)
  6. (3xy^2z^2)(15x^2yz^3)

Multiply and simplify.

  1. x^8 (xy^3+3x)
  2. 2x(4x-5)
  3. 6ab(-10a^2 b^3+c^5)
  4. 9x^3(3x^2-2x+7)
  5. -3a^2b(9a^2-4b^2)

Mixed Review

  1. Give an example of a fourth degree trinomial in the variable n .
  2. Find the next four terms of the sequence 1,\frac{3}{2},\frac{9}{4},\frac{28}{8}, \ldots
  3. Reece reads three books per week.
    1. Make a table of values for weeks zero through six.
    2. Fit a model to this data.
    3. When will Reece have read 63 books?
  1. Write 0.062% as a decimal.
  2. Evaluate ab\left ( a+\frac{b}{4} \right ) when a=4 and b=-3 .
  3. Solve for s : 3s(3+6s)+6(5+3s)=21s .

Image Attributions

Explore More

Sign in to explore more, including practice questions and solutions for Multiplication of Monomials by Polynomials.


Please wait...
Please wait...

Original text